Islamic Finance and Economic Development: The Impact of the Islamic Finance Sector on Indonesia’s Economic Development - Zainur Zainur (JOURNAL OF SHARIA ECONOMICS, 2021)
The re-existence of Islamic economics on the surface of the earth makes a major contribution to the new economic system, with new models and innovations that are applied according to the conditions it goes through without reducing the values that must be implemented in the Islamic economic system. Although it can be understood that this Islamic economic system is not a new thing, but has experienced a new history in the modern era This research aimed to describe the models and applications of sharia-based financial models in the economy, Islamic finance models that are able to promote equitable development, and the impact of the Islamic finance sector on economic development. This was qualitative research with document analysis. The results were financial system in Islam has an impact on economic growth, especially in Indonesia, it can be felt the level of difference between conventional economics and Islamic economics. In addition to the investment factor made by investors, the contract model that is applied bears the risk for both parties, because with a contract like this the level of prudence that must be carried out is more selective compared to other contracts. In addition to Islamic banking, non-bank financial institutions also have a very significant role in increasing economic growth. Among non-bank financial institutions that have an influence on economic growth are zakat, baitul maal wattamwil, waqf and others.